Strategi Dalam Membuka Rekening Online Pada Bank Syariah Indonesia Di Kalangan Mahasiswa Jakarta - Sarah Putri Nadin; Siti Ning Farida (Journal of Islamic Economics and Finance, 2024)
The development of the Islamic banking sector in Indonesia reflects a response to the public's need for a banking system that not only provides sound financial services, but also adheres to sharia principles. PT Bank Syariah Indonesia as a major player in this sector has to face the changes that occur due to high competition in an effort to win customer trust and support. Currently, customer behaviour in the Indonesian banking industry is very diverse. Low administrative costs are also an important consideration for customers. The importance of these factors in customer decision-making has been recognised by modern banks, which now realise that customers do not only consider interest rates or financial benefits, but also want the sophistication and full features of banking products. Technological advancement, especially in mobile banking, has become a significant trend, not only in developed countries but also in developing countries such as Indonesia. Mobile banking, as one of the service products offered by PT Bank Syariah Indonesia, is an important factor in students' decision to open an account online. The existence of good virtual services from Bank Syariah Indonesia, especially through the mobile banking platform, is a major attraction for students, given their dependence on technology and the need for convenience in transactions.